2013
DOI: 10.1111/ajo.12079
|View full text |Cite
|
Sign up to set email alerts
|

Maternal outcomes in women supplemented with a high-protein drink in labour

Abstract: In labour, patient satisfaction is improved with high-protein drink supplementation compared with ice chips/water with comparable gastric emptying rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Two other papers included in this review showed that GE was not influenced by epidural anesthesia [54,56]. However, since these studies included only a small number (24) of patients, firm recommendations about fasting prior to epidural anesthesia cannot be made.…”
Section: Gastric Emptying In Obstetricsmentioning
confidence: 94%
See 1 more Smart Citation
“…Two other papers included in this review showed that GE was not influenced by epidural anesthesia [54,56]. However, since these studies included only a small number (24) of patients, firm recommendations about fasting prior to epidural anesthesia cannot be made.…”
Section: Gastric Emptying In Obstetricsmentioning
confidence: 94%
“…Three studies were performed in pregnant women [54][55][56]. One study showed that during labour performed under epidural anesthesia, antral area decreased from 319 mm 2 at epidural insertion to 203 mm 2 at full cervical dilatation, with a median between the two measurements of 188 min; gastric motility was preserved during labor [54].…”
Section: Gastric Emptying In Obstetricsmentioning
confidence: 99%
“…Findings from semi‐structured, in‐depth interviews; informal observations; and field notes demonstrated that women were disappointed by the restriction of food and drink during labor and believed that the promotion of comfort was an essential need during labor. In the same year, US investigators randomized 150 women in labor into 2 groups: members of one group received a high‐protein drink (325 mL) with ice chips or water as needed, and members of the control group received only ice chips or water as needed . Outcome measures included incidences of nausea and emesis, rate of gastric emptying, and patient satisfaction.…”
Section: Women's Preferences For Nutrition During Labormentioning
confidence: 99%
“…In the same year, US investigators randomized 150 women in labor into 2 groups: members of one group received a high-protein drink (325 mL) with ice chips or water as needed, and members of the control group received only ice chips or water as needed. 57 Outcome measures included incidences of nausea and emesis, rate of gastric emptying, and patient satisfaction. Rates of gastric emptying were comparable, and there were no differences in the incidence of nausea or emesis or other co-morbidities; women who ingested the high-protein drink had higher satisfaction scores.…”
Section: Etiology Of Higher Risk For Aspirationmentioning
confidence: 99%